Characterization of a novel cellular defect in patients with phenotypic homozygous familial hypercholesterolemia - Norman, Dennis (American Society for Clinical Investigation, 1999)
Familial hypercholesterolemia (FH) is characterized by a raised concentration of LDL in plasma that results in a significantly increased risk of premature atherosclerosis. In FH, impaired removal of LDL from the circulation results from inherited mutations in the LDL receptor gene or, more rarely, in the gene for apo B, the ligand for the LDL receptor. We have identified two unrelated clinically homozygous FH patients whose cells exhibit no measurable degradation of LDL in culture. Extensive analysis of DNA and mRNA revealed no defect in the LDL receptor, and alleles of the LDL receptor or apo B genes do not cosegregate with hypercholesterolemia in these families. FACS(®) analysis of binding and uptake of fluorescent LDL or anti–LDL receptor antibodies showed that LDL receptors are on the cell surface and bind LDL normally, but fail to be internalized, suggesting that some component of endocytosis through clathrin-coated pits is defective. Internalization of the transferrin receptor occurs normally, suggesting that the defective gene product may interact specifically with the LDL receptor internalization signal. Identification of the defective gene will aid genetic diagnosis of other hypercholesterolemic patients and elucidate the mechanism by which LDL receptors are internalized.